Gut microbiota remodeling drived by dietary millet protein prevents the metabolic syndrome - Shuhua Shan; Ruopeng Yin; Jiangying Shi; Lizhen Zhang; Jiaqi Zhou; Qinqin Qiao; Xiushan Dong; Wenjing Zhao; Zhuoyu Li (Food Science and Human Wellness)
Metabolic syndrome (MetS) is a chronic disease associated with the disturbance of gut microbiota homeostasis. Metabolites derived from gut microbes play essential roles in MetS prevention and therapy. Here, we focused on the inhibitory effect of the extract of millet bran protein (EMBP) on a high-fat diet (HFD)-induced MetS, aiming to identify gut microbiota and their metabolites that involve in the anti-MetS activity of EMBP. The obesity, chronic inflammation, insulin resistance in MetS mouse models were abolished after EMBP treatment. The protective mechanism of EMBP against HFD-induced MetS may depend on improved gut barrier function. Using microbiome analysis, we found that EMBP supplementation improved gut microbiome dysbiosis in MetS mice, specifically upregulating Bacteroides acidifaciens. The fecal microbiota transplantation (FMT) also demonstrated this phenomenon. In addition, metabolomic analysis showed that EMBP mediates metabolic profiling reprogramming in MetS mice. Notably, a microbiota-derived metabolite, gamma-aminobutyric acid (GABA), is enriched by EMBP. In addition, exogenous GABA treatment produced a similar protective effect to EMBP by improving NRF2-dependent gut barrier function to protect HFD-induced MetS. The results suggest that EMBP suppress host MetS by remodeling of gut microbiota as an effective candidate for next-generation medicine food dual purpose dietary supplement to intervene in MetS.